1972
DOI: 10.1002/aic.690180432
|View full text |Cite
|
Sign up to set email alerts
|

Effect of axial dispersion on microbial growth

Abstract: The extent of microbial growth in a continuous flow reactor is influenced by various degrees of fluid mixing which may range from one extreme of plug-flow to the other extreme of completely mixed flow. To assess the effect of mixing on the extent of microbial growth various flow models such as the tanks-in-series model and the axial dispersion model are often employed. Such flow models have been successfully applied to biological waste treatment processes by Murphy (1971) and Lee et al. (1971).The purpose of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Most studies reported thus far have indicated that the axial dispersion coefficieiit in an unpacked bubble column is independent of liquid velocity. Chen ( 1972), however, reported that this observation is due to the fact that in all studies, the interstitial liquid velocity has been less than 10% of the rising velocity of the bubbles ub. At U L > 0.1Ub, Chen (1972) presented the dependency of the dispersion coefficient 011 the liquid velocity as…”
Section: 25-3 30-220mentioning
confidence: 80%
“…Most studies reported thus far have indicated that the axial dispersion coefficieiit in an unpacked bubble column is independent of liquid velocity. Chen ( 1972), however, reported that this observation is due to the fact that in all studies, the interstitial liquid velocity has been less than 10% of the rising velocity of the bubbles ub. At U L > 0.1Ub, Chen (1972) presented the dependency of the dispersion coefficient 011 the liquid velocity as…”
Section: 25-3 30-220mentioning
confidence: 80%
“…With sterile feed operation (C,,=O), eqn (4) for the bottom stage reduces to and the respective equations for other stages are the same as eqns ( 5 ) and (6). The solution in this case is given by cx,i= 0 (28)…”
Section: Sterile Feedmentioning
confidence: 99%